Donor-matched comparison of chondrogenic progenitors resident in human infrapatellar fat pad, synovium, and periosteum - implications for cartilage repair. (2nd November 2019) - Mantripragada, V. P.; Piuzzi, N. S.; Bova, W. A.; Boehm, C.; Obuchowski, N. A.; Lefebvre, V.; Midura, R. J.; Muschler, G. F.
ABSTRACT: Purpose : There is a clinical need to better characterize tissue sources being used for stem cell therapies. This study focuses on comparison of cells and connective tissue progenitors (CTPs) derived from native human infrapatellar fatpad (IPFP), synovium (SYN), and periosteum (PERI). Materials and Methods : IPFP, SYN, PERI were harvested from twenty-eight patients undergoing arthroplasty. CTPs were quantitatively characterized using automated colony-forming-unit assay to compare total nucleated cell concentration—[Cell], cells/mg; prevalence-(PCTP ), CTPs/million nucleated cells; CTP concentration—[CTP], CTPs/mg; proliferation and differentiation potential; and correlate outcomes with patient's age and gender. Results : [Cell] did not differ between IPFP, SYN, and PERI. PCTP was influenced by age and gender: patients >60 years, IPFP and SYN had higher PCTP than PERI ( p < 0.001) and females had higher PCTP in IPFP ( p < 0.001) and SYN ( p = 0.001) than PERI. [CTP] was influenced by age: patients <50 years, SYN ( p = 0.0165) and PERI ( p < 0.001) had higher [CTP] than IPFP; patients between 60 and 69 years, SYN ( p < 0.001) had higher [CTP] than PERI; patients >70 years, IPFP ( p = 0.006) had higher [CTP] than PERI. In patients >60 years, proliferation potential of CTPs differed significantly (SYN>IPFP>PERI); however, differentiation potentials were comparable between all three tissue sources. Conclusion : SYN and IPFP may serve as a preferred tissue source for patients >60 years, and PERI along with SYN and IPFP may serve as a preferred tissue source for patients <60 years for cartilage repair. However, the heterogeneity among the CTPs in any given tissue source suggests performance-based selection might be useful to optimize cell-sourcing strategies to improve efficacy of cellular therapies for cartilage repair.